Pengaruh Keragaman Produk Dan Persepsi Harga Terhadap Impulse Buying - Damayanti, Najwa Nafiz; Sanita Dhakirah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid growth of the retail industry in Indonesia, particularly in Malang, has intensified competition among retailers. Swalayan Enak Eco Karangploso seeks to attract customers by offering a wide variety of products and competitive prices. However, no prior research has specifically examined how product variety and price perception influence impulse buying in this supermarket. This study aims to analyze the effect of product variety and price perception on impulse buying at Swalayan Enak Eco Karangploso.This research employed a quantitative approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The t-test results for the product variety variable showed that t-count > t-table (3.033 > 1.661), indicating that product variety has a positive effect on impulse buying. The t-test results for the price perception variable also showed that t-count > t-table (4.876 > 1.661), meaning that price perception positively affects impulse buying. Furthermore, the F-test results revealed that product variety and price perception simultaneously have a positive and significant effect on impulse buying, as evidenced by F-count > F-table (47.485 > 3.09). The coefficient of determination (R²) was 0.484, which means that 48.4% of impulse buying is influenced by product variety and price perception, while the remaining 51.6% is affected by other factors. In conclusion, product variety and price perception simultaneously influence impulse buying at Swalayan Enak Eco Karangploso, with price perception contributing the most. It is recommended that the supermarket maintain and further optimize its competitive pricing strategy to enhance impulse purchases.